2020
DOI: 10.1002/chem.202001870
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Performance of a High‐Voltage LiNi0.5Mn1.5O4 Cathode in a Carbonate‐Based Electrolyte with a Novel and Low‐Cost Functional Additive

Abstract: Butyric anhydride (BA) is used as an effective functional additive to improve the electrochemical performance of a high‐voltage LiNi0.5Mn1.5O4 (LNMO) cathode. In the presence of 0.5 wt % BA, the capacity retention of a LNMO/Li cell is significantly improved from 15.3 to 88.4 % after 200 cycles at 1 C. Furthermore, the rate performance of the LNMO/Li cell is also effectively enhanced, and the capacity goes up to 112 mAh g−1 even at 5 C, which is considerably higher than that of a LNMO/Li cell in electrolyte wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…Therefore, spinel LiNi 0.5 Mn 1.5 O 4 cathode has been considered as the most important candidate materials in LIBs for high working voltage (∼4.7 V vs Li/Li + ) and high energy density (∼650 W h kg –1 ). However, conventional dilute electrolytes with lithium salt of 1mol L –1 (1 M) are prone to excessive decomposition in the process of matching this high-voltage cathode materials (>4.7 V), resulting in an increased irreversible capacity such as low initial Coulombic efficiency, poor cyclic stability, and low safety . To date, many efforts from the perspective of electrolytes have been made to solve this problem mainly including using additives such as borates, phosphonates, and acid anhydride, and introducing oxidation-resistant auxiliary solvents, such as propylene carbonate (PC), sulfones, and nitriles. However, the starting point of these methods have the problem of incompatibility between the electrolyte and the electrode. , Therefore, it is significantly important to deeply understand the oxidation decomposition mechanism of the electrolyte and find an effective strategy to improve the compatibility of electrolyte solutions with high-voltage cathode materials in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spinel LiNi 0.5 Mn 1.5 O 4 cathode has been considered as the most important candidate materials in LIBs for high working voltage (∼4.7 V vs Li/Li + ) and high energy density (∼650 W h kg –1 ). However, conventional dilute electrolytes with lithium salt of 1mol L –1 (1 M) are prone to excessive decomposition in the process of matching this high-voltage cathode materials (>4.7 V), resulting in an increased irreversible capacity such as low initial Coulombic efficiency, poor cyclic stability, and low safety . To date, many efforts from the perspective of electrolytes have been made to solve this problem mainly including using additives such as borates, phosphonates, and acid anhydride, and introducing oxidation-resistant auxiliary solvents, such as propylene carbonate (PC), sulfones, and nitriles. However, the starting point of these methods have the problem of incompatibility between the electrolyte and the electrode. , Therefore, it is significantly important to deeply understand the oxidation decomposition mechanism of the electrolyte and find an effective strategy to improve the compatibility of electrolyte solutions with high-voltage cathode materials in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…The CEI film can effectively suppress the dissolution of transition metal cations, prevent the decomposition of the electrolytes, and finally improve the cyclic ability of LNMO-based LIBs. In our previous work, we found that the butyric anhydride (BA) as a film-forming additive can also construct a stable LNMO interphase film and further enhance the electrochemical properties of LNMO at a voltage from 3.5 to 4.9 V. 36 Subsequently, it was revealed that, in the CEI film, there exists a remarkable difference in the microstructure, stability, and function when anhydrides have different molecular structures as film-forming additives. 37 Furthermore, Li's group found that 4-fluorophenyl acetate as the additive can improve the stability of the solid electrolyte interphase more efficiently, due to the aromatic ring.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, developing cathode materials with high operating voltage is an effective way to improve the energy density of LIBs, such as olivine LiMPO 4 (M=Mn, Ni, Co), layered nickel‐rich LiNi x Co y Mn 1‐x‐y O 2 (x≥0.8) and lithium‐rich xLi 2 MnO 3 ⋅ (1‐x)LiMO 2 (M=Mn, Ni, Co, Fe, Cr, etc. ), as well as spinel LiNi 0.5 Mn 1.5 O 4 (LNMO) [2] . Among them, LiNi 0.5 Mn 1.5 O 4 material has attracted more attention due to high operating voltage (∼4.7 V vs .…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of new‐energy vehicle industry, the demand for lithium‐ion batteries (LIBs), as the main power supply for electric vehicles, is growing rapidly [1] . The energy density of LIBs is determined by specific capacity and operating voltage [2] . Therefore, developing cathode materials with high operating voltage is an effective way to improve the energy density of LIBs, such as olivine LiMPO 4 (M=Mn, Ni, Co), layered nickel‐rich LiNi x Co y Mn 1‐x‐y O 2 (x≥0.8) and lithium‐rich xLi 2 MnO 3 ⋅ (1‐x)LiMO 2 (M=Mn, Ni, Co, Fe, Cr, etc.…”
Section: Introductionmentioning
confidence: 99%